Food Handlers’ Safety Knowledge and Its Impact on Personal Hygiene and Disease Control Practices - Stephen, Kwol Victoria (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Building on the knowledge, attitude and practice model, this thesis investigated the role of food handlers in adherence to hygienic-sanitary standards for food safety. Specifically, using data gathered from food handlers in restaurants, hotels and hospitals, the study examined the effect of food handlers’ safety knowledge on their hygienic-sanitary practices of personal hygiene, kitchen hygiene and disease control measures. It also checked the mediating role of food handlers’ attitudes in the causal relationship between food safety knowledge and the hygienic-sanitary practices of food handlers. Empirical findings supported the hypothesized assumptions that food safety knowledge positively impacts food handler’s attitudes and attitudes in turn significantly contributes to the adherence to hygienic-sanitary conditions for food safety. Further, other than the indirect effect of handler’s attitude on food safety knowledge and personal hygiene, food handlers’ attitude partially mediates the effect of knowledge on kitchen hygiene and disease control measure. Implications for managers, government and academicians were also discussed. Keywords: Food safety knowledge, personal hygiene, kitchen hygiene, hospitality, Nigeria

ÖZ: Bilgi, tutum ve uygulama modeline dayanarak, bu tez, gıda işleyicilerinin gıda güvenliği için hijyenik sağlık standartlarına uymadaki rolünü araştırmıştır. Özellikle, restoranlarda, otellerde ve hastanelerde gıda işleyicilerinden toplanan veriler kullanılarak, gıda işleyicilerinin güvenlik bilgilerinin kişisel hijyen, mutfak hijyeni ve hastalık kontrol önlemlerinin hijyenik sağlık uygulamaları üzerindeki etkisi incelenmiştir. Ayrıca, gıda işleyicilerinin gıda güvenliği bilgisi ile gıda işleyicilerinin hijyenik sağlık uygulamaları arasındaki nedensel ilişkideki tutumlarının aracılık rolünü de kontrol etmiştir. Ampirik bulgular, gıda güvenliği bilgisinin gıda işleyicisinin tutum ve tutumlarını pozitif yönde etkilediğine dair varsayımları desteklemiştir ve bu da gıda güvenliği için hijyenik sağlık koşullarına uymaya önemli ölçüde katkıda bulunmuştur. Ayrıca, işleyicinin gıda güvenliği bilgisi ve kişisel hijyen konusundaki tutumunun dolaylı etkisinden başka, gıda işleyicilerinin tutumu kısmen bilginin mutfak hijyeni ve hastalık kontrol önlemi üzerindeki etkisine aracılık eder. Ayrıca yöneticiler, hükümet ve akademisyenler için de sonuçlar tartışılmıştır. Anahtar Sözcükler: Gıda güvenliği bilgisi, kişisel hijyen, mutfak hijyeni, misafirperverlik, Nijerya
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Prof. Dr. Turgay Avcı.
Keywords: Tourism; Food Safety--Personal Hygiene--Tourism; Food safety knowledge; personal hygiene; kitchen hygiene; hospitality; Nigeria